2020
DOI: 10.1186/s12891-020-03391-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of femoral implant design modification on anterior knee pain and patellar crepitus in patients who underwent total knee arthroplasty without patella resurfacing

Abstract: Background: The incidence of patient dissatisfaction due to anterior knee pain (AKP) and patellar crepitus after total knee arthroplasty (TKA) remains a concern. However, it has been shown that improvements in the femoral component of traditional prostheses could reduce these instances of pain in the case of TKA performed with patellar resurfacing. This study aims to investigate whether TKA without patellar resurfacing can also benefit from the aforementioned femoral component modification in reducing AKP and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(2) perioperative factors such as postoperative pain control; (3) medical factors such as a history of substance abuse, Parkinson disease, and/or diabetes mellitus; and (4) technical factors such as alignment and stability of the knee [6][7][8] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) perioperative factors such as postoperative pain control; (3) medical factors such as a history of substance abuse, Parkinson disease, and/or diabetes mellitus; and (4) technical factors such as alignment and stability of the knee [6][7][8] .…”
mentioning
confidence: 99%
“…Even though TKA is one of the most effective operations in orthopaedic surgery, 20% to 30% of patients who have TKA experience residual symptoms after surgery 3-5 . A variety of factors have been implicated in this dissatisfaction rate: (1) patient-specific factors such as preoperative expectations; (2) perioperative factors such as postoperative pain control; (3) medical factors such as a history of substance abuse, Parkinson disease, and/or diabetes mellitus; and (4) technical factors such as alignment and stability of the knee 6-8 .…”
mentioning
confidence: 99%
“…Similarly, although insignificant ( p = 0.1475 and 0.228), the incidence of AKP was less in Attune versus PFC-Sigma knees in both the FBRD and the FBRE group in our study. Similarly, past studies [ 27 , 28 ] have shown that the incidence of AKP was less in patients with Attune implant in comparison with that in patients with PFC-Sigma implant.…”
Section: Discussionmentioning
confidence: 52%
“…Our study shows that CR-type prostheses with patellar resurfacing result in less improvement on the functional outcome measures (KOOS-PS and OKS). Some studies suggest that more modern "patella-friendly" femoral designs outperform other TKA designs by reducing AKP and patellar complications in the unresurfaced knees (25,26). We compared resurfaced and unresurfaced knees for several surgical systems and saw no benefit of patellar resurfacing.…”
Section: Discussionmentioning
confidence: 96%